Odpowiedź :
Hejka!
Poziom A :
4 • x - 3 + 5 • x = 15
4x - 3 + 5x = 15
4x + 5x = 15 + 3
9x = 18 / : 9
x = 2
5x + 7 - 3 • x = 13
5x - 3x = 13 - 7
2x = 6 / : 2
x = 3
7 • x - 2 - 6 • x = 5
7x - 6x = 5 + 2
x = 7
6 • x - 4 + 4 • x = 56
6x + 4x = 56 + 4
10x = 60 / : 10
x = 6
Poziom B :
6 • x = 2 - x - 8
6x + x = 2 - 8
7x = -6 / : 7
x = -6/7
8 • x = 9 + 5 • x
8x - 5x = 9
3x = 9 / : 3
x = 3
7 • x = 2 • x - 20
7x - 2x = -20
5x = -20 / : 5
x = -4
2 • x = 12 - 2 • x
2x + 2x = 12
4x = 12 / : 4
x = 3
Poziom C :
8 - 3 • x = 6 • x - 10
-3x - 6x = -10 - 8
-9x = -18 / : (-9)
x = 2
7 • x - 4 = 9 + 8 • x
7x - 8x = 9 + 4
-x = 13 / : (-1)
x = -13
-5 + 7 • x = 2x - 20
7x - 2x = -20 + 5
5x = -15 / : 5
x = -3
8 - 2 • x = -4 + 2 • x
-2x - 2x = -4 - 8
-4x = -12 / : (-4)
x = 3
Pozdrawiam! - Julka
A
4 • x - 3 + 5 • x = 15
4x - 3 + 5x = 15
4x + 5x = 15 + 3
9x = 18 / : 9
x = 2
5x + 7 - 3 • x = 13
5x - 3x = 13 - 7
2x = 6 / : 2
x = 3
7 • x - 2 - 6 • x = 5
7x - 6x = 5 + 2
x = 7
6 • x - 4 + 4 • x = 56
6x + 4x = 56 + 4
10x = 60 / : 10
x = 6
B
6 • x = 2 - x - 8
6x + x = 2 - 8
7x = -6 / : 7
x = -6/7
8 • x = 9 + 5 • x
8x - 5x = 9
3x = 9 / : 3
x = 3
7 • x = 2 • x - 20
7x - 2x = -20
5x = -20 / : 5
x = -4
2 • x = 12 - 2 • x
2x + 2x = 12
4x = 12 / : 4
x = 3
C
8 - 3 • x = 6 • x - 10
-3x - 6x = -10 - 8
-9x = -18 / : (-9)
x = 2
7 • x - 4 = 9 + 8 • x
7x - 8x = 9 + 4
- x = 13 / : (-1)
x = -13
-5 + 7 • x = 2x - 20
7x - 2x = -20 + 5
5x = -15 / : 5
x = -3
8 - 2 • x = -4 + 2 • x
-2x - 2x = -4 - 8
-4x = -12 / : (-4)
x = 3